Pengaruh Penggunaan Fitur Virtual Try On, Brand Image, Dan Electronic Word Of Mouth Terhadap Keputusan Pembelian Produk Make Over Pada E-Commerce - Isnaini Retno Wulandari; Hendra Prasetya (PRAGMATIS, 2026)
This research aims to analyze the influence of Virtual Try-On features, Brand Image, and Electronic Word of Mouth (e-WOM) on purchase decisions for Make Over products in e-commerce among female students at the Faculty of Economics and Business, Wijaya Kusuma University, Surabaya. Employing a quantitative approach with survey methods, the study utilized purposive sampling to select 100 respondents who had previously purchased Make Over products and utilized the Virtual Try-On feature. Data were collected via questionnaires and analyzed using multiple linear regression with SPSS software. The results demonstrate that Virtual Try-On, Brand Image, and Electronic Word of Mouth each have a positive and significant partial effect on purchase decisions, with Electronic Word of Mouth identified as the dominant influencing factor. These findings suggest that companies should optimize their digital marketing strategies by enhancing Virtual Try-On technology and strengthening brand image through consistent quality and communication; furthermore, this study provides a reference for future research to explore additional relevant variables.